Data Storage: Air‐Stable Cesium Lead Iodide Perovskite for Ultra‐Low Operating Voltage Resistive Switching (Adv. Funct. Mater. 5/2018). (29th January 2018) - Han, Ji Su; Le, Quyet Van; Choi, Jaeho; Hong, Kootak; Moon, Cheon Woo; Kim, Taemin Ludvic; Kim, Hyojung; Kim, Soo Young; Jang, Ho Won
Abstract : Cesium lead iodide (CsPbI3 ) perovskite, an all‐inorganic halide perovskite, is synthesized on a platinum‐coated silicon substrate for an ultra‐low operating voltage resistive switching memory device by Soo Young Kim, Ho Won Jang, and co‐workers in article number1705783 . An electrochemical metallization mechanism involving metal conducting filaments is proposed to explain the resistive switching behavior which can be applied to next‐generation synaptic devices.